Transcendental Leadership in Leader’s Strategies Management Under the 21st Century Dynamics Era - Jedaman, Pornchai; Kenaphoom, Sanya; Udompan, Angkana (Interdisciplinary Academic and Research Journal, 2022)
The strategies management of having the deep and broad foresight, value for personnel and continuous improvement, sincerity to stakeholders, focus on innovation development, resource efficiency, use of appropriate technology, truth-based risk reduction, knowledge sharing, and corporate culture building from to knowledge create and understanding with the personnel educational administration to adaptation and working of effectiveness. Therefore, effective organizational strategies require effective leadership. The transcendental leadership in leader’s strategies management under the 21st-century dynamics era of ability to motivate the personnel of a working potential to succeed and achieve the organizational goals. A “Key” dimensions of sustainable transcendental leadership include leadership spirits, visions, morals and ethics, pursuing services, and leader competencies.